Strategi Pengembangan Desa Pelaga Sebagai Destinasi Agrowisata di Kabupaten Badung - Komang Ema Marsitadewi (Politicos: Jurnal Politik Dan Pemerintahan, 2021)
Badung Regency is more dominated by beach tourism. More than ten famous beaches in Bali are in Badung Regency. These beaches are only located in a few districts in Badung Regency. Inequality between sub-districts also occurs between areas that have tourism potential such as beaches and areas that have other tourism potential such as waterfalls or other tourism. This will create new problems for Badung Regency in the future. In fact, sub-districts that do not have coastal tourism potential have challenges as well as opportunities to develop. One of them is Petang District, Pelaga Village. This village does not have beach tourism but has other natural potentials that can be used as an attraction for tourists to come and visit Pelaga Village. These potential differences must be implemented which can then be used as opportunities for Pelaga Village. The purpose of this research is to produce a strategy to develop Pelaga Village as a tourism destination. This research is a qualitative research with a descriptive approach. Data obtained from primary data and secondary data. The data is then processed using data triangulation techniques to reduce the researcher's subjectivity and is also analyzed using SWOT analysis to produce a development strategy. In this study, it was found that Pelaga Village has a lot of potential for agro-tourism and can be developed such as asparagus and some hydroponic plants. . Not only that, the community's high interest in developing agro-tourism also supports the development of Pelaga Village. After assessing the potential that is owned by the opportunity, the threat from Pelaga Village came up with several development strategies for Pelaga Village, namely to further activate the community, especially farmer groups in developing their agro products. increasing the existence of the Agricultural Culture Festival in Pelaga Village, refining the missing destination components such as the availability of restaurants and inns, creating an organization that can bring together various farmer groups in Pelaga Village, in relation to the community in developing and managing the potentials of Pelaga Village.